Eksistensi Madrasah di Tengah Popularitas Sekolah Islam Terpadu: Studi Historisitas, Rivalitas, dan Kontinuitasnya di Kota Medan - Rahmat Rifai Lubis; Dairina Yusri; Mursal Aziz (Sekolah Tinggi Agama Islam Sumatera Medan, 2022)
This study aims to analyze the historicity of madrasas and integrated Islamic schools, the forms of rivalry between the two, and the continuity of madrasas amid the popularity of integrated Islamic schools in Medan. The research method used is qualitative, based on phenomenological studies. The results of the study show that (1) Historically the madrasas in the city of Medan are older than the Integrated Islamic Schools. Madrasas in Medan City have existed since before independence, namely in 1918, while the Integrated Islamic School only appeared in the 1990s. (2) The rivalry between madrasah and integrated Islamic schools occurs naturally because both have similarities in the delivery of education. Forms of rivalry in several aspects (a) the acquisition of the number of students, (b) curriculum, (c) learning, (d) financing of education, (e) facilities and infrastructure, (f) standardization of human resources. This rivalry has caused a decline in the image and presence of madrasas in society, and other facts show that several madrasas had to close due to the absence of students enrolling. However, this rivalry only occurs and has an impact on the status of private institutions, (3) the continuity of madrasas in the midst of the popularity of integrated Islamic schools is very dependent on the ability to maintain heritage and consistency in knowledge which are the characteristics of both. In addition, the transfer of authority from the Ministry of Education and Culture to the Ministry of Religion for integrated Islamic schools can be a solution so that a special policy for integrated Islamic schools is born.